The centenary of the March on Rome: between legacy and oblivion - Goffredo Adinolfi (Political Outbreaks against the Liberal Order (1917-1940), 2022)
The March on Rome is one of the most iconic events in the history of the XX century. The fall of thousands of squadristi on Rome unleashed the authoritarian outbreak and paved the way to the so called “corporatist century”. Thousands of pages have been written about the takeover of Rome. And even more will be written because the way how started the fascist transition is not just an event but is also a narrative. After a century the controversies that surround the March on Rome could not be entirely resolved: the fear for the socialist rise, the unfinished process of democratization, the role and the collapse of the liberal parties, the role of the King Vittorio Emanuele III and, clearly the legacies in post-fascist parties.